Protein interaction analysis of senataxin and the ALS4 L389S mutant yields insights into senataxin post-translational modification and uncovers mutant-specific binding with a brain cytoplasmic RNA-encoded peptide. - Craig L Bennett (Public Library of Science (PLoS), 2013)
Senataxin is a large 303 kDa protein linked to neuron survival, as recessive mutations cause Ataxia with Oculomotor Apraxia type 2 (AOA2), and dominant mutations cause amyotrophic lateral sclerosis type 4 (ALS4). Senataxin contains an amino-terminal protein-interaction domain and a carboxy-terminal DNA/RNA helicase domain. In this study, we focused upon the common ALS4 mutation, L389S, by performing yeast two-hybrid screens of a human brain expression library with control senataxin or L389S senataxin as bait. Interacting clones identified from the two screens were collated, and redundant hits and false positives subtracted to yield a set of 13 protein interactors. Among these hits, we discovered a highly specific and reproducible interaction of L389S senataxin with a peptide encoded by the antisense sequence of a brain-specific non-coding RNA, known as BCYRN1. We further found that L389S senataxin interacts with other proteins containing regions of conserved homology with the BCYRN1 reverse complement-encoded peptide, suggesting that such aberrant protein interactions may contribute to L389S ALS4 disease pathogenesis. As the yeast two-hybrid screen also demonstrated senataxin self-association, we confirmed senataxin dimerization via its amino-terminal binding domain and determined that the L389S mutation does not abrogate senataxin self-association. Finally, based upon detection of interactions between senataxin and ubiquitin-SUMO pathway modification enzymes, we examined senataxin for the presence of ubiquitin and SUMO monomers, and observed this post-translational modification. Our senataxin protein interaction study reveals a number of features of senataxin biology that shed light on senataxin normal function and likely on senataxin molecular pathology in ALS4.